ICN – CELEBRATING THE RICH AND DIVERSE INDONESIAN CULTURE - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PENANG, 19 November 2016 – The Indonesia Cultural Night (ICN) 2016 once again showcased the rich